Quantitative ecotoxicology - Newman, Michael C. (CRC Press, 2013)
"This book provides a quantitative treatment of the science of ecotoxicology. The first chapters consider fundamental concepts and definitions essential to understanding the fate and effects of toxicants at various levels of ecological organization as covered in the remaining chapters. Scientific ecotoxicology and associated topics are defined. The historical perspective, rationale, and characteristics are outlined for the strong inferential and quantitative approach advocated in this book. The general measurement process is discussed, and methodologies for defining and controlling variance, which could otherwise exclude valid conclusions regarding ecotoxicological endeavors, are considered.Ecotoxicological concepts at increasing levels of ecological organization are discussed in the second part of the book. Quantitative methods used to measure toxicant effects are outlined in this section. The final chapter summarizes the book with a brief discussion of ecotoxicological assessment. Numerous figures and tables accompany text, with many statistical tables found in the appendix for quick reference. Although the book primarily focuses on aquatic systems, with appropriate modification the concepts and methods can be applied to terrestrial systems"-- Provided by publisher.
Keywords: Pollution -- Environmental aspects -- Measurement.; Environmental toxicology -- Mathematics.; elektronické knihy; electronic books